2004
DOI: 10.1074/jbc.m406697200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Interaction Sites between Na,K-ATPase and FXYD Proteins

Abstract: Several members of the FXYD protein family are tissue-specific regulators of Na,K-ATPase that produce distinct effects on its apparent K ؉ and Na ؉ affinity. Little is known about the interaction sites between the Na,KATPase ␣ subunit and FXYD proteins that mediate the efficient association and/or the functional effects of FXYD proteins. In this study, we have analyzed the role of the transmembrane segment TM9 of the Na,K-ATPase ␣ subunit in the structural and functional interaction with FXYD2, FXYD4, and FXYD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
2
11

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 39 publications
9
72
2
11
Order By: Relevance
“…We have recently provided evidence for an interaction between the transmembrane segment of FYXD proteins and the ninth transmembrane segment of the ␣-subunit (22). A similar position of FXYD protein is supported by other approaches (31) while other locations have also been proposed recently (32).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We have recently provided evidence for an interaction between the transmembrane segment of FYXD proteins and the ninth transmembrane segment of the ␣-subunit (22). A similar position of FXYD protein is supported by other approaches (31) while other locations have also been proposed recently (32).…”
Section: Discussionsupporting
confidence: 56%
“…2A) a negative slope of the K 1/2 K ext ϩ vs. Vm relation in the high negative potential (Ϫ50 to Ϫ130 mV) in the presence of extracellular sodium (Na ext ϩ ), which is due to the competitive binding of Na ext ϩ with K ext ϩ on the E2 conformation. Alanine substitution of E960, a residue predicted to mediate the interaction between the ␣-subunit and FXDY7 (22), had only a small effect, whereas the E961A mutation resulted in a large change of the voltage-dependent activation by K ext ϩ in the presence of Na ext ϩ ( Fig. 2 A) whereas there was no effect in the absence of Na ext ϩ (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Previously, the location of the trans-membrane segment in the groove between M2, M6, and M9 was inferred on the basis of electron microscopy of renal Na ϩ ,K ϩ -ATPase (20), functional effects of mutations in M9 (22), and cross-linking of the cytoplasmic domain of the ␥ subunit to S4 of the ␣1 subunit (23). Specifically, the current experiments show that Cys-49 of CHIF is cross-linked to Cys-140 in M2 of the ␣ subunit, because either the C49F or the C140S mutation specifically interferes with the crosslink.…”
Section: Oligomeric State Of ␣/␤ Subunits and Fxyd Proteins-the Resulmentioning
confidence: 99%
“…A denaturation study also suggested that ␥ might interact in the M8 to M10 region (21). A role for M9 of the ␣ subunit has been inferred from the effects of mutants in M9 on the stability of ␣/␤-␥, ␣/␤-CHIF, or ␣/␤-FXYD7 complexes, and the functional consequences of the mutations have been studied in Xenopus oocytes (22). Modeling of the FXYD helix was consistent with docking in the groove between M2, M6, and M9 in the ␣ subunit.…”
mentioning
confidence: 99%
“…Plusieurs localisations avaient été proposées pour ce troisième site. C'est en cherchant à préciser la nature des interactions entre la sous-unité α de la Na + ,K + -ATPase et une protéine régulatrice -de la famille des protéines FXYD [6] -que nous avons découvert le rôle très important joué par un segment transmembranaire peu étudié jusque-là, M9, dans la mécanique du transport des cations. À la suite de l'observation de l'influence très importante d'une mutation (E961C) dans le segment M9 sur la Figure 1.…”
unclassified